County Business Patterns, 2002 (United States): U.S. Summary, State, and County Data ([Verlag nicht ermittelbar], 2008)
These County Business Patterns files contain data from counties across the United States in 2002. Variables include state, county, total employees, and total wages. Also provided are data on the number of establishments by employment size class.